Human Capital Development as a Driver of Sustainable Development: The Mediating Role of Innovation Capability in the UAE - Al-Blooshi, Mariam Mohammed; Jalil, Muhammad Hilmi; Mohamad, Abu Dardaa (International Review of Management and Marketing, 2025)
Despite increasing recognition of human capital development (HCD) as a foundation for national progress, little is known about how it accelerates sustainable development outcomes. Prior studies have primarily examined human capital from an economic perspective, overlooking the mechanisms that transform workforce investments into broader sustainability outcomes. To address this gap, this paper aims to explore the mediating role of innovation capability on the relationship between HCD and sustainable development, conceptualized through economic, social, and environmental dimensions. Drawing upon resource-based and capability perspectives, this study develops and tests the proposed model using data collected from 384 employees working in government organizations in the United Arab Emirates. Structural equation modeling was applied to examine direct and indirect relationships. The results reveal that HCD exerts a significant positive effect on sustainable development. Moreover, innovation capability was found to mediate this relationship by enabling knowledge, skills, and competencies to translate into economic, social, and environmental sustainability outcomes. This study is among the first to analyze the mediating role of innovation capability on the relationship between HCD and sustainable development in the context of the United Arab Emirates. The findings contribute to theory by integrating HCD with sustainability research and provide practical implications for policymakers seeking to align workforce strategies with national sustainability agendas.